2019
DOI: 10.1002/jbm.a.36612
|View full text |Cite
|
Sign up to set email alerts
|

Combination of bioactive factors and IEIK13 self‐assembling peptide hydrogel promotes cartilage matrix production by human nasal chondrocytes

Abstract: Nasal reconstruction remains a challenge for every reconstructive surgeon. Alloplastic implants are proposed to repair nasal cartilaginous defects but they are often associated with high rates of extrusion and infection and poor biocompatibility. In this context, a porous polymeric scaffold filled with an autologous cartilage gel would be advantageous. In this study, we evaluated the capacity of IEIK13 self‐assembling peptide (SAP) to serve as support to form such cartilage gel. Human nasal chondrocytes (HNC) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 46 publications
0
17
0
Order By: Relevance
“…It is well-known that amplification of chondrocytes induces their dedifferentiation [38] and we have previously reported that the FI cocktail, besides its proliferative effect on HACs, also stimulates their dedifferentiation [16]. We have also shown that, after FI-induced dedifferentiation, the BIT cocktail can drive redifferentiation of human nasal chondrocytes seeded in self-assembling peptide hydrogel [39] and of HACs seeded in porous collagen sponge [16,23], with production of type II collagen and other cartilage-characteristic molecules such as type IX collagen and sulfated proteoglycans.…”
Section: Discussionmentioning
confidence: 94%
“…It is well-known that amplification of chondrocytes induces their dedifferentiation [38] and we have previously reported that the FI cocktail, besides its proliferative effect on HACs, also stimulates their dedifferentiation [16]. We have also shown that, after FI-induced dedifferentiation, the BIT cocktail can drive redifferentiation of human nasal chondrocytes seeded in self-assembling peptide hydrogel [39] and of HACs seeded in porous collagen sponge [16,23], with production of type II collagen and other cartilage-characteristic molecules such as type IX collagen and sulfated proteoglycans.…”
Section: Discussionmentioning
confidence: 94%
“…Twenty‐six articles were found to involve TE applications for nasal reconstruction since 2014 (Figure 3). While the total study number is relatively small, these studies present a suitable evaluation of histologic characteristics, mechanical properties, regenerative potential, and the ability to create a 3D construct using primarily in vitro and small in vivo models 8,10‐19 . There has been an absence of testing in large animal models, however, there have been multiple attempts (four studies) to replace nasal cartilage subunits in humans 9,20‐22 …”
Section: Discussionmentioning
confidence: 99%
“…Heatmap representing the proportion of publications by year that utilized specific translational research methodologies from construct characterization to human trial to investigate nasal tissue engineering 8‐24,98‐106 …”
Section: Discussionmentioning
confidence: 99%
“…SAP hydrogels provide a three‐dimensional (3‐D) environment that fosters proliferation and migration of many types of cells 9,10 . They have been shown not to elicit immunogenic or inflammatory responses 11‐13 . An SAP hydrogel, RADA16, has been proposed as a scaffold because it has unique 3‐D structure 6,14 .…”
Section: Introductionmentioning
confidence: 99%
“…9,10 They have been shown not to elicit immunogenic or inflammatory responses. [11][12][13] An SAP hydrogel, RADA16, has been proposed as a scaffold because it has unique 3-D structure. 6,14 In pre-clinical models, bone regeneration was achieved by using RADA16.…”
Section: Introductionmentioning
confidence: 99%